Analisis Nilai Tambah dan Karakteristik Pemasaran Cumi Asin Studi Kasus UMKM CV Indo Ikan Pratama Bandung - junianto, junianto junianto; Junianto, Junianto (LPPM Universitas Malikussaleh - Indonesia, 2025)
The fisheries sector has abundant fish resource potential, both in terms of quantity and type, thus contributing significantly to Indonesia's economic recovery and development efforts. One of the processed products from fishery resources is salted fish. Salted fish has the advantage of a long shelf life and has added value. This study aims to analyze the added value and marketing characteristics of dried salted squid products produced by the MSME CV. Indo Ikan Pratama in Cileunyi District, Bandung Regency. The research method used is descriptive quantitative with the Hayami approach to calculate the added value. Direct observation and interviews with MSME owners served as primary data, while secondary data were collected from various literature sources. Based on the analysis that has been done, the added value of processing wet salted squid into dried salted squid is IDR 33,200/kg. The value added ratio is 30.97%. The marketing characteristics of dried salted squid, carried out by the Indo Ikan Pratama UMKM targets medium to large scale shops in the Greater Bandung area (geographically), the product's advantages lie in its longer shelf life and clean and neat packaging. Pricing is determined using the line pricing method. Door-to-door promotion, a direct approach that involves visiting each store. Distribution is carried out directly from the factory to the sales outlets. CV. Indo Ikan Pratama continues to innovate and maintain product quality to remain competitive in the market.